Investigating The Effects Of Brand Relationship Quality On Consumer Brand Sabotage Through Mediating Effect Of Negative Emotion - Saba Qasim, Salniza Salleh , Hasnizam Shaari (International Journal of Advanced Science and Technology, 2020)
he purpose of this study is to investigate the relationship between brand relationship quality and consumerbrand sabotage through mediating effect of negative emotion. This study addresses the issues regardingconsumer brand sabotage. The proposed model is supported by stimulus organism response (S-O-R) theory.The theoretical framework helps future researchers to get better understanding of constructs and supportto apply in other service contexts